Seedling and Seed Ordering System: A PWA Prototype Implementation - Yana Shintya; Riama Santy Sitorus; Roby Darmadi (Journal of Information Systems and Informatics)
Air pollution in urban areas is a significant global challenge, and Jakarta is one of Southeast Asia's most polluted major cities. Efforts to address this problem are through the greening of urban areas. The Jakarta Special Region Seed and Plant Protection Development Center (PPBPT) is vital in providing and distributing plant seeds to the community. However, ordering manual seeds is still a significant obstacle to effective and efficient distribution. This research aims to develop a prototype application of Progressive Web Applications (PWA) based seed and seed ordering information system. Using the Extreme Programming (XP) method in this research, the PWA application provides a new perspective to accelerate the handling of urban environmental problems while providing reliable public digital services. The application development cycle with the XP method produces good software with faster turnaround time, lower costs, and responsiveness to user needs. The research results in an information system prototype application with various functions, such as user registration, identity verification, seedling ordering, stock management, and order history. The system proved to automate the seedling ordering process significantly, thus improving stock management efficiency and seedling distribution in 18 gardens under PPBPT. Indirectly, the results of this research support urban greening and contribute to improving air quality in Jakarta. Furthermore, the application can be developed by adding various forms of digital technology to help urban greening in different forms of support or other public service applications.